Efficiency of four different dietary preparation methods in extracting functional compounds from dried tangerine peel. (15th August 2019) - Zhang, Huijuan; Cui, Jiefen; Tian, Guifang; DiMarco-Crook, Christina; Gao, Wei; Zhao, Chengying; Li, Genyuan; Lian, Yunhe; Xiao, Hang; Zheng, Jinkai
Highlights: It is the first report to explore the effect of 4 dietary preparation methods on DTP. Synthetic evaluation model of DTP extract was established for the first time. The optimum conditions for soaking were 4 min, 80 °C, 1:31 g/mL and extraction for twice. Ethanol extraction showed the best extraction efficiency among the 4 dietary preparation methods. Electronic eye and electronic tongue can differentiate DTP extracts. Abstract: Dried tangerine peel (DTP) is an excellent plant resource that has been used as ingredients for both food and traditional Chinese medicine. In this study, the efficiency of four different dietary preparation methods (i.e. soaking, boiling, steaming, and ethanol extraction) in extraction of functional compounds (i.e. flavonoids and essential oil constituents) from DTP was evaluated systematically for the first time. To conduct a comprehensive evaluation of the extraction of the functional compounds, a synthetic evaluation model based on a weighting method was established. The optimum conditions of each dietary preparation method (e.g., time, temperature, solid-liquid ratio, etc.) were determined by response surface methodology. Ethanol extraction showed the best extraction efficiency, followed by soaking, boiling, and steaming. Additionally, different DTP extracts were shown to be clearly distinguished by electronic eye and electronic tongue. This research provides essential findings for the effective dietary instruction of DTP consumption.